Telisik Faktor-Faktor Pengaruh Return Saham - Budiastuti, Susanti; Awaludin, Dipa Teruna; Yaqin, Nurul; Sudewi, Pipin Sri; Suseno, Suseno (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The study aims to determine the effect of leverage, profitability, company size and liquidity on the company's stock returns of the healtcare sector listed on the IDX in 2022-2024. The sampling method used is non probability sampling with purposive sampling technique. The sample used in this study was 20 companies. Sampling using purposive sampling, using multiple linear regression methods. The results of this study indicate that the variable leverage, profitability, company size and liquidity both partially and simultaneously have a positive and significant effect on the company's stock returns around the healthcare. R Square of 0.3149 shows that 31.49 % of stock return variables can be explained by leverage, profitability, company size and liquidity variables, while the remaining 68.51 % are explained by other variables that are not explained in this study.